A neurobiological pathway to smoking in adolescence: TTC12-ANKK1-DRD2 variants and reward response - Macare, Christine; Banaschewski, Tobias; Flor, Herta (European neuropsychopharmacology, 2018)
The TTC12-ANKK1-DRD2 gene-cluster has been implicated in adult smoking. Here, we investigated the contribution of individual genes in the TTC12-ANKK1-DRD2 cluster in smoking and their association with smoking-associated reward processing in adolescence. A meta-analysis of TTC12-ANKK1-DRD2 variants and self-reported smoking behaviours was performed in four European adolescent cohorts (N=14,084). The minor G-allele of rs2236709, mapping TTC12, was associated with self-reported smoking (p=5.0×10−4) and higher plasma cotinine levels (p=7.0×10−5). This risk allele was linked to an increased ventral-striatal blood-oxygen level-dependent (BOLD) response during reward anticipation (n=1,263) and with higher DRD2 gene expression in the striatum (p=0.013), but not with TTC12 or ANKK gene expression. These data suggest a role for the TTC12-ANKK1-DRD2 gene-cluster in adolescent smoking behaviours, provide evidence for the involvement of DRD2 in the early stages of addiction and support the notion that genetically-driven inter-individual differences in dopaminergic transmission mediate reward sensitivity and risk to smoking.
Gesehen am 07.08.2019